Simulation as a Tool for Assessing Physics Students' Academic Performance and Interest in Rivers State - Ntaka, Nduka Nkechi; Amadi, Reginald Okechukwu (Faculty of Natural and Applied Sciences Journal of Applied and Physical Sciences, 2024)
The research study adopted the pre-test, post-test, quasi-experimental and descriptive survey design, because, the study described, Simulation, as an influencer in assessing Physics students’ academic performance and interest in Rivers –State, on 3 experimental methods - Interactive, System Dynamics and Role- play simulation on Physics students’ academic performance and interest and in Rivers-State. Three research questions and three hypotheses guided the study while the population of the study was made up of the entire senior secondary school two Physics consisting of 480 students in four out of ten co-educational public senior secondary schools in Rivers-state). The sample size consisted of 160 senior secondary two (SS2) Physics students and a control /intact SS2 Physics classroom, made up of the discussion groups selected using the purposive sampling technique based on functionality and equipped Physics laboratory. Two instruments were used in this research, the Simulation Physics Performance Test (SPPT) and the Simulation Physics Interest Questionnaire (SPIQ). The Kuder-Richardson (KR-21) formulae were used to ascertain the academic performance of Physics students at 0.86 reliability coefficient index while the Cronbach-Alpha formula was used for the interest of the students at a correlation coefficient of 0.82 while the Physics Interest questionnaires (PIQ) was analyzed using the SSPL to elicit the interest of Physics. The research questions were answered using the mean and standard deviation while the hypotheses were tested using the ANOVA to compare the difference between the mean interest scores of students taught Physics using the Interactive, System Dynamic, Role-play over the Discussion Group. The result of the experiment showed that the discussion method overruled other forms of simulation in their interest in Physics while the interactive simulation had a significant difference in the academic performance of Physics students. It was recommended among others that, adequate and standard technological facilities should be provided as a supportive resource material, to stir up the interest of Physics students through direct communication while the use of simulation should be used to stir up the academic performance of students to ensure efficiency.